Boletim cultural - Junta Distrital de Lisboa (Junta Distrital de Lisboa)
Existências: S.2 nº 55-54 (1960)- S.3 nº 65-66 (1966) S.3 nº 83 (1977) S.3 nº 84 (1978) S.3 nº 85 (1979) S.3 nº 86 (1980), 1º tomo S.3 nº 86 (1980), 2º tomo dir. Maria Micaela R. T. Soares~ S. 2 - Semestral S. 3 - Anual